Mitochondrial Protein Import Motor: the ATPase Domain of Matrix Hsp70 Is Crucial for Binding to Tim44, while the Peptide Binding Domain and the Carboxy-Terminal Segment Play a Stimulatory Role - Krimmer, Thomas (American Society for Microbiology, 2000)
The import motor for preproteins that are targeted into the mitochondrial matrix consists of the matrix heat shock protein Hsp70 (mtHsp70) and the translocase subunit Tim44 of the inner membrane. mtHsp70 interacts with Tim44 in an ATP-dependent reaction cycle, binds to preproteins in transit, and drives their translocation into the matrix. While different functional mechanisms are discussed for the mtHsp70-Tim44 machinery, little is known about the actual mode of interaction of both proteins. Here, we have addressed which of the three Hsp70 regions, the ATPase domain, the peptide binding domain, or the carboxy-terminal segment, are required for the interaction with Tim44. By two independent means, a two-hybrid system and coprecipitation of mtHsp70 constructs imported into mitochondria, we show that the ATPase domain interacts with Tim44, although with a reduced efficiency compared to the full-length mtHsp70. The interaction of the ATPase domain with Tim44 is ATP sensitive. The peptide binding domain and carboxy-terminal segment are unable to bind to Tim44 in the absence of the ATPase domain, but both regions enhance the interaction with Tim44 in the presence of the ATPase domain. We conclude that the ATPase domain of mtHsp70 is essential for and directly interacts with Tim44, clearly separating the mtHsp70-Tim44 interaction from the mtHsp70-substrate interaction.